ANTIMICROBIAL USAGE IMPLEMENTATION AND AWARENESS OF POULTRY LAYER PRODUCERS IN CEBU, PHILIPPINES - Mondejar, Hershey P; Contratista, Melvin B (Journal of Agriculture and Technology Management, 2022)
Antimicrobial resistance is resistance in different types of organisms facilitated by inappropriate use of medicines. A face to face survey questionnaire applied to 30 poultry layer producers located in Bantayan, Sta.Fe, and Madridejos, Cebu, Philippines was conducted. Most of the surveyed farms were large scale, operated by well- educated individuals who have extensive experiences in layer business operation. Based on the results, the antimicrobial use (AMU) of all antibiotics considered in this study have satisfactorily implemented for poultry layer medication as feed supplement and for therapeutic use except with fair implementation on quinolones and fluoroquinolones. Layer chicken producers and managers have high level of awareness on the classification of antibiotics on β-Lactams, aminoglycosides and aminocyclitols, quinolones and fluoroquinolones, tetracyclines, and macrolides and lincosamides; while a medium level of awareness on polypeptides, amphenicols, sulphonamides and trimethoprim. On the average, there have had high level of awareness on proper dosage use of antibiotics and practicing drug withdrawal period; medium level of awareness on presence of antibiotic residues in table eggs, on effects of antibiotic residues to human health, and rotation of antibiotic usage to avoid antimicrobial resistance (AMR) effects; and lack of awareness on residues may have direct effect to consumers and on the effects that the ingestion of food on the intestinal microflora of humans. It is proposed that the issues of AMU and AMR can be overcome by communicating with all stakeholders and discussing the need for surveillance of AMU and AMR.